Persepsi Generasi Milenial terhadap Pekerjaan di Bidang Pertanian (Studi Kasus di Desa Dalang, Kecamatan Selemadeg Timur, Kabupaten Tabanan) - UTAMI, PUTU ANINDITHA CAHYA; PITANA, I GDE; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Millenialls Perception Of Work in Agricultural Sector (Case Study in Dalang Village, Selemadeg Timur District, Tabanan Regency).  Millennials refers to generation of people born between 1980 until 2000 and characterized by high frequency use of technology, information and communication. The growth of technology, information and communication not only give positive effects to millennials, but also negative effects such as millennials’ bad perception of agriculture. The aims of this research are to analyze millennials’ perception on agriculture and also the reason of millennials working in agriculture in Dalang Village, Selemadeg Timur District, Tabanan Regency. A total sample of 84 persons were selected using non-proportional stratified random sampling and simple random sampling. Data were collected using survey method and descriptive statistic is used to analyze the data. This research shows that millennials’ perception of agriculture is bad, which mean they think that working in agricultural sector can’t give job satisfaction. This research also shows that millennials’ reasons to work in agricultural sector are because they lost their job during pandemic Covid-19, the lack of education and skills. Agriculture jobs is chosen to continue managing their family agricultural land as the last chances.